1979
DOI: 10.1002/cne.901840104
|View full text |Cite
|
Sign up to set email alerts
|

An autoradiographic examination of corticocortical and subcortical projections of the mediodorsal‐projection (prefrontal) cortex in the rat

Abstract: The efferent connections of the cortex projected upon by the mediodorsal thalamic nucleus (MD-projection cortex) have been re-examined autoradiographically in the rat following the microelectrophoretic injection of 3H-proline-leucine into different parts of the medial and sulcal MD-projection cortex. Contrary t o previous negative findings, the present experiments revealed a system of extensive corticocortical projections and indicated that different areas of the MD-projection cortex have distinctive patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

29
243
3
3

Year Published

1987
1987
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 780 publications
(278 citation statements)
references
References 34 publications
29
243
3
3
Order By: Relevance
“…On the other hand, the areas around the rhinal sulcus, such as the lateral orbitofrontal cortex (LO) and the dorsal part of the agranular insular cortex (AID), constitute the lateral prefrontal cortex in rats, because they have reciprocal connections to the mediodorsal thalamic nucleus (Zilles and Wree 1995;Fuster 1997) which is a main anatomical criterion for belonging to the PFC. Although LO and AID have projection fibers to the dorsal raphe nucleus in rats (Peyron et al 1998;Beckstead 1979), these fibers, unlike those originating from mPFC, probably have no functional relevance for the serotonergic neurotransmission, because electrical stimulation of AID and LO did not alter hippocampal 5-HT output in the present study. There are two reasons for this functional difference between medial and lateral PFC: first, the medial PFC sends significantly more efferent fibers to the dorsal raphe nucleus than LO and AID; and second, only the medial PFC projects to the whole of the dorsal raphe nucleus (Peyron et al 1998).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…On the other hand, the areas around the rhinal sulcus, such as the lateral orbitofrontal cortex (LO) and the dorsal part of the agranular insular cortex (AID), constitute the lateral prefrontal cortex in rats, because they have reciprocal connections to the mediodorsal thalamic nucleus (Zilles and Wree 1995;Fuster 1997) which is a main anatomical criterion for belonging to the PFC. Although LO and AID have projection fibers to the dorsal raphe nucleus in rats (Peyron et al 1998;Beckstead 1979), these fibers, unlike those originating from mPFC, probably have no functional relevance for the serotonergic neurotransmission, because electrical stimulation of AID and LO did not alter hippocampal 5-HT output in the present study. There are two reasons for this functional difference between medial and lateral PFC: first, the medial PFC sends significantly more efferent fibers to the dorsal raphe nucleus than LO and AID; and second, only the medial PFC projects to the whole of the dorsal raphe nucleus (Peyron et al 1998).…”
Section: Discussionmentioning
confidence: 48%
“…Consistent with this hypothesis, it has been demonstrated that rat medial prefrontal cortex (prelimbic area) has dense efferent projections to both the dorsal and the median raphe nuclei (Aghajanian and Wang 1977;Beckstead 1979;Wyss and Sripanidkulchai 1984;Sesack et al 1989;Behzadi et al 1990;Peyron et al 1998). Thus, it is possible that PFC stimulation activates the raphe nuclei leading to increased -HT levels in terminal areas.…”
Section: Discussionmentioning
confidence: 65%
“…Addictive behaviors are thought to result from persistent molecular and cellular neuroadaptations in the mesocorticolimbic circuit that follow exposure to drugs of abuse. The mesocorticolimbic circuit includes dopamine (DA) neurons in the ventral tegmental area (VTA) that project to the nucleus accumbens (NAcc) and prefrontal cortex (Beckstead, 1979;Christie et al, 1985;Oades and Halliday, 1987;Carr and Sesack, 1996). Nearly all addictive drugs share the ability to cause DA release at nerve terminals in the NAcc (Di Chiara and Imperato, 1988), and this shared property of drugs with different molecular targets may be responsible for setting into motion maladaptive processes that underlie addiction (Koob, 1992;Nestler, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The rat PFC receives cortical afferents which arise in secondary sensory areas, motor areas and paralimbic cortices (van Eden et al 1992), and it projects to various cortical and subcortical structures, e.g. midbrain, nucleus accumbens (ACC) and anteromedial striatum (Leonard 1969;Beckstead 1979;Sesack and Pickel 1992). Furthermore, the PFC receives a dopaminergic innervation from mesocortical dopamine (DA) cells (Bj6rklund and Lindvall 1984) and DAergic axon terminals exhibit synaptic contacts mainly with pyramidal neurons in deeper cortical layers (Verney et al 1990).…”
Section: Introductionmentioning
confidence: 99%